INNOVATION IN DISABILITY-FRIENDLY IMMIGRATION SERVICES THROUGH THE IMPLEMENTATION OF BRAILLE CORNER SERVICES AT THE CLASS I NON-TPI IMMIGRATION OFFICE IN BOGOR - KARTIKA, AYU (Jurnal Abdimas Imigrasi, 2025)
Inclusive public service is one of the main indicators in realizing respect for human rights, including the right of persons with disabilities to obtain equal access to information. In the immigration environment, access to procedural information is often not fully accessible to visually impaired individuals. Based on this condition, an innovation in the form of implementing a Braille Corner service at the Class I Non-TPI Bogor Immigration Office is proposed as an alternative solution to create disability-friendly services. This research aims to examine the urgency and relevance of implementing the Braille Corner in the context of immigration public services through a literature study approach. The method used is a literature review of various scientific sources, government policies, laws and regulations, and good practices in disability services in the public sector. The results of the study indicate that the implementation of the Braille Corner has the potential to provide significant benefits, including increased accessibility of immigration information for visually impaired applicants, strengthening the institution's image as humane and inclusive, and contributing to the fulfillment of the principles of Human Rights-Based Public Services (P2HAM). In addition, this service can also be a strategic step in supporting bureaucratic reform and accelerating services that are adaptive to the needs of vulnerable groups. The conclusion of this research recommends that the Ministry of Law and Human Rights, especially the Directorate General of Immigration, begin to consider piloting the Braille Corner service as a form of disability-friendly immigration service innovation that can be replicated nationally.